Stability of the principles of minimal specificity and maximal buoyancy - Thanh, Do Van (Journal of Computer Science and Cybernetics, 2016)
The aim of this paper is to investigate an use of the principles of minimal Specificity and maximal Buoyancy (MB) proposed by R.R.Yager and to introduced some conditions of a set of possibility distributions and weights which guarantee uniqueness of possibility distribution selected by the use of these principles from a given set of distributions.